Development of Central Diabetes Insipidus in a Female Victim with Severe Brain Injury - N. V. Nikiforova; I. K. Ratkin; Yu. A. Churlyaev; R. S. Turygin; S. V. Arkhipova; G. N. Averchinkova (Общая реаниматология, 2009)
Case report. A pregnant woman with severe brain injury developed cerebral salt-wasting syndrome concurrent with diabetes insipidus. Placental enzymatic destruction of antidiuretic hormone and thyroid, adrenal, and renal dysfunction were excluded. Polyuria developed on day 3 when diuresis was less than 8.5 liters, there was hyponatremia (Na+ < 130 mmol/l) with a urinary Na+ content of > 40 mmol/l. The administration of 3% sodium chloride solution considerably enhanced polyuria. When minirin was given in a daily dose of 0.4 mg, diuresis reached 32.4 liters, which exceeds the levels described for the complete absence of antidiuretic hormone. The use of minirin in the mean therapeutic dose (0.6 mg daily) reduced, but failed to normalize diuresis. Evident hypernatremia and hypokalemia were absent in the existing polyuria. Brain injury in the female patient was suspected to cause and impair the synthesis of antidiuretic hormone and to increase the elaboration of ouabaine. This concomitance led to the concurrent development of central diabetes insipidus and cerebral salt-wasting syndrome. On this basis, the dose of minirin was increased up to 1.2 mg daily; hypothiazid 50 mg twice daily was prescribed. Hydrocortisone 50 mg twice daily was intramuscularly injected after diuresis reduced to 4.7 liters and hyponatremia (Na+ = 112.2 mmol/l). The performed therapy could normalize diuresis up to 1.8 liters and correct the blood levels of electrolytes. Key words: brain injury, diabetes insipidus, cerebral salt-wasting syndrome.